Consumers’ barriers towards Bluetooth-enabled advertising - Piret-Gerard, Julie (2012)
This study carries forward the exploration of consumers’ acceptance and barriers towards Bluetooth-enabled advertising by identifying the full range of elements taking part in this research question through a qualitative method of inquiry. This investigation took the form of six key questions probing for: (1) consumers’ acceptance to turn on the Bluetooth function on their mobiles; (2) their responses to Bluetooth ads; (3) their behaviour following on the reception of those ads; (4) the factors impacting their responses; (5) their concerns towards the system; (6) and their acceptance of ads popping-up while they are texting. In respect of the methodology, twenty-five young Belgian adults were interviewed with the help of a data collection mind-map as well as different visual stimulus probing for the above mentioned themes. Participants were brought into two scenarios where they would hypothetically receive two Bluetooth ads, for a place to eat and for a clothing store, in an imaginary shopping centre. Overall, the level of awareness towards the Bluetooth technology was very high amongst the participants. When used as an advertising channel, all respondents would have positive reactions towards the two hypothetical advertising messages. However, nine of the twenty-five participants would refuse to turn on the Bluetooth function on their mobiles when seeing the Bluetooth opt-in panel. Mobile advertisers need therefore to understand what could motivate consumers to opt-in and how to act on users’ concerns towards the system, as further developed in this dissertation.